Editor's choice - Pinder RM (Dove Medical Press, 2012)
Roger M PinderEditor-In-Chief, Neuropsychiatric Disease and TreatmentSchizophrenia remains one of the most debilitating and intractable illnesses in psychiatry. Despite the availability of effective drug treatment since the beginning of the psychopharmacological era in the early 1960s with the introduction of the first antipsychotic chlorpromazine, the subsequent development of second generation or atypical antipsychotics, and the effectiveness of certain types of psychotherapy, many patients are unresponsive and remain unwell for several years or relapse after apparent response. Only clozapine has proven efficacy in treatment-resistant schizophrenia, but many patients still do not respond. Polypharmacy is common, with many physicians choosing to augment rather than switch medications. Schizophrenia may be in part a neurodevelopmental disorder and involve changes in brain structure, and credence has been given to the idea that the prodromal phase, before overt symptoms have appeared, should already have been addressed with aggressive treatment. Various aspects of schizophrenia and its treatment, as well as the associated use of antipsychotic drugs in the treatment of the manic phase of bipolar disorder and Tourette syndrome, have been covered in the pages of Neuropsychiatric Disease and Treatment during the first half of 2012.